The Enhancing English Language Teaching Through Phonetic-Based Assessment Strategies among Iraqi EFL Students - Al- Yasir , Sahar Sabbar Zamil (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study investigates the impact of phonetic-based assessment strategies on enhancing English language proficiency among Iraqi EFL (English as a Foreign Language) students. This study uses a mixed-method approach, combining quantitative surveys and qualitative interviews with 150 undergraduate students from the University of Al-Turath. Quantitative data were gathered through structured tests and phonetic assessments, while qualitative data were obtained from semi-structured interviews examining students’ experiences and attitudes toward phonetic learning. The findings show that phonetic-based assessment enhances students’ pronunciation accuracy, listening comprehension, and language confidence, while also increasing motivation and engagement through clear guidance and corrective feedback. The study underscores the need to systematically integrate phonetic evaluation into English language curricula, with recommended practices including minimal pair activities, phoneme-focused drills, and regular pronunciation assessment. Although limited to a single university context, this research contributes evidence-based insights for improving pronunciation instruction and assessment in EFL higher education in Iraq